THE USE OF APHORISMS IN THE EDUCATIONAL PROCESS: THEIR ROLE IN ENHANCING TEACHING AND LEARNING - Jo’raqulova Hurmatoy (TADQIQOTLAR, 2025)
Annotation:This article explores the role of aphorisms in the educational process, focusing on their pedagogical significance and cultural value. Aphorisms are examined as concise forms of wisdom that not only enrich classroom instruction but also foster critical thinking and moral development among learners. The study highlights how aphorisms from Uzbek and English traditions reflect universal human values while preserving cultural identity. It further emphasizes the potential of aphorisms to motivate students, stimulate discussion, and connect theoretical knowledge with real-life experiences. The article argues that incorporating aphorisms into teaching can enhance both intellectual growth and ethical education, making them a valuable resource for modern pedagogy.